2022
DOI: 10.3389/fnins.2022.826547
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Luteal Olfactory Abilities Reveal Healthy Women’s Emotional and Cognitive Functions

Abstract: Ovarian hormones modulate women’s physical and psychological states periodically. Although the olfactory function is increasingly recognized as a reflection of physical and mental health conditions in the clinic, the role of olfaction in emotional and cognitive functions for healthy individuals has yet to be elucidated, especially when taking the menstrual cycle into account. We carried out a comprehensive investigation to explore whether the menstrual cycle could modulate women’s olfactory function and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Brain health-related parameters will include the following: (1) brain structure using anatomical T1-weighted imaging and diffusion tensor imaging; (2) cognitive assessment36–38 using resting-state fMRI, and with n-back and flanker tasks on behavioural experiments and task-based fMRI; (3) food preference evaluation using a Go/No-go task on behavioural experiments and task-based fMRI39 and scales; and (4) olfaction assessment using a set of olfactory tests40 that can assess olfactory threshold, identification and discrimination function. These olfactory tests were created by the Institute of Psychology, Chinese Academy Sciences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain health-related parameters will include the following: (1) brain structure using anatomical T1-weighted imaging and diffusion tensor imaging; (2) cognitive assessment36–38 using resting-state fMRI, and with n-back and flanker tasks on behavioural experiments and task-based fMRI; (3) food preference evaluation using a Go/No-go task on behavioural experiments and task-based fMRI39 and scales; and (4) olfaction assessment using a set of olfactory tests40 that can assess olfactory threshold, identification and discrimination function. These olfactory tests were created by the Institute of Psychology, Chinese Academy Sciences.…”
Section: Discussionmentioning
confidence: 99%
“…(3) food preference evaluation using a Go/No-go task on behavioural experiments and task-based fMRI 39 and scales; and (4) olfaction assessment using a set of olfactory tests 40 that can assess olfactory threshold, identification and discrimination function. These olfactory tests were created by the Institute of Psychology, Chinese Academy Sciences.…”
Section: Brain Health-related Parametersmentioning
confidence: 99%
“…It was shown that idiopathic repeated pregnancy loss was associated with altered olfactory responses to body odor [7]. At the same time, hormone changes across the women's menstrual cycle may lead to changes in perception of chemical signals or other odors and hormonal responses to these cues [10,11].…”
Section: Introductionmentioning
confidence: 99%